Architecture Australia. - Royal Australian Institute of Architects (North Sydney : Publications of the RAIA, 1976)
Special edition on Indigenous housing.
Supplement: Architectural product news.
APAIS, Australia public affairs information service
APAIS. This database is available on the Informit Online Internet Service: http://www.informit.com.au
Architectural periodicals index
Australian Public Affairs - Full Text until December 2013
Avery index to architectural periodicals. Second edition. Revised and enlarged. Supplement
From 1989- each Oct. issue entitled: Architext directory.
Keywords: Architecture -- Periodicals; Architecture -- Australia -- Periodicals; Housing